Osiolek - Jarmolkiewicz, Elzbieta (Zielona Gora : Wydawn. E. Jarmolkiewicz, 1993)
Two farm children see a newborn donkey, which they befriend. Ages 4-7.
Board book.
Cover title.
Keywords: Donkeys -- Juvenile fiction